Mapping of the Spinal Sensorimotor Network by Transvertebral and Transcutaneous Spinal Cord Stimulation - Shkorbatova, Polina; Lyakhovetskii, Vsevolod; Pavlova, Natalia; Popov, Alexander; Bazhenova, Elena; Kalinina, Daria; Gorskii, Oleg; Musienko, Pavel (Frontiers in Systems Neuroscience, 2020)
Transcutaneous stimulation is a neuromodulation method that is efficiently used for recovery after spinal cord injury and other disorders that are accompanied by motor and sensory deficits. Multiple aspects of transcutaneous stimulation optimization still require testing in animal experiments including the use of pharmacological agents, spinal lesions, cell recording etc. This need initially motivated us to develop a new approach of transvertebral spinal cord stimulation (SCS) and to test its feasibility in acute and chronic experiments on rats. The aim of the current work was to study the selectivity of muscle activation over the lower thoracic and lumbosacral spinal cord when the stimulating electrode was located intravertebrally and to compare its effectiveness to that of the clinically used transcutaneous stimulation. In decerebrated rats, electromyographic activity was recorded in the muscles of the back (m.longissimus dorsi), tail (m. abductor caudae dorsalis) and hindlimb (mm. iliacus, adductor magnus, vastus lateralis, semitendinosus, tibialis anterior, gastrocnemius medialis, soleus and flexor hallucis longus) during SCS with an electrode placed alternately in one of the spinous processes of the VT12–VS1 vertebrae. The recruitment curves for motor and sensory components оf the evoked potentials (separated from each other by means of double-pulse stimulation) were plotted for each muscle; their slopes characterised the effectiveness of the muscle activation.The electrophysiological mapping demonstrated that transvertebral SCS has specific effects to the rostrocaudally distributed sensorimotor network of the lower thoracic and lumbosacral cord, mainly by stimulation of the roots that carry the sensory and motor spinal pathways. These effects were compared in the same animals when the mapping was performed by transcutaneous stimulation, and a similar distribution of muscle activity and underlying neuroanatomical mechanisms were found. The experiments on chronic rats validated the feasibility of the proposed stimulation approach of transvertebral SCS for further studies.